Metformin promotes in vitro maturation of oocytes from aged mice by attenuating mitochondrial oxidative stress via SIRT3-dependent SOD2ac - Cao, Yongzhi; Wang, Zhao; Zhang, Changming; Bian, Yuehong; Zhang, Xin; Liu, Xin; Chen, Wendi; Zhao, Yueran (Frontiers in Cell and Developmental Biology, 2022)
Human female fecundity irreversibly decreases with age, adversely affecting oocyte quality, worsening pregnancy outcomes, and increasing the incidence and severity of birth defects. The first-line type 2 diabetes treatment metformin has been associated with delayed aging and reduction of oxidative stress. However, it remains unclear if metformin confers any benefits for aged oocytes, particularly in the context of the assisted human reproductive technology (ART) known as in vitro maturation (IVM). In this study, we found that adding metformin to an IVM culture medium of aged oocytes significantly improved both oocyte maturation and early embryonic development. This study demonstrates that metformin reduced the extent of meiotic defects and maintained a normal distribution of cortical granules (CGs). RNA-seq analysis of metformin-treated oocytes revealed genes involved in reducing mitochondrial ROS. Additionally, the results found that metformin improved mitochondrial function, reduced apoptosis, increased the extent of autophagy, and reduced mitochondrial ROS via the SIRT3-mediated acetylation status of SOD2K68 in the oocytes of aged mice. As such, our findings demonstrated that metformin exhibits a protective effect against the decreased quality of aged oocytes, which can potentially improve ART success rates and represents a potential strategy for preventing or delaying reproductive aging.